Feminist Urbanism - Eva Youkhana; Cilia Saed Hedayatiy (Alternautas, 2023)
Buenos Aires is globally appealing for its diverse culture, history, and opportunities. It lures people for employment, education, and healthcare, adding to urbanization tensions. The city administration advertises integrative urbanism to improve attractiveness but struggles with high crime rates, particularly compared to some European cities.